Association of geohelminths infection and asthma in elementary school children in Kalibaru, North Jakarta - Jaya A Effendi; Mardjanis Said; Partini P Trihono (Indonesian Pediatric Society, 2010)
Background Asthma inflammation process and geohelminthinfection have the same immune response. Epidemiological studiesin developed countries show the increased asthma prevalenceand decreased geohelminth infection, while developing countriesusually have low asthma prevalence but high geohelminthinfection.Objectives To determine asthma proportion in children withgeohelminth infection and relationship between asthma andgeohelminth prevalence of elementary school students in NorthJakarta.Method A cross sectional study was done in February 2009 at anElementary School in North Jakarta. Asthma was diagnosed usingISAAC questionnaire which was answered by parents. We didfecal analysis using ether formaline test to establish geohelminthinfection.Results The proportion of students with asthma was 11.5%(33 of 286 children). Most of them were male, aged 6-10 yearsold, and well nourished. Geohelminth infection was foundin 71.9%of the students. Most of children with geohelminthinfection were male (55%), aged 6-10 years old (63%), and wellnourished (64%). Proportion of asthma in children with andwithout geohelminth infection is 12.6% and 8.8%, respectively.Geohelminth infection consisted of ascariasis (80%), trichuriasis(39%), and ankylostomiasis (9%). There was no significantrelationship between asthma and geohelminth infection(P=0.357), nor between asthma and ascariasis (P=0.202), asthmaand trichiuriasis (P=0.133).Conclusions The occurrence of asthma in children withgeohelminth infection is 12.6% and there is no difference ofasthma incidence among children with or without geohelminthinfection.